2012
DOI: 10.1182/blood-2011-08-375816
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial hyperpermeability induces the clinical symptoms of Clarkson disease (the systemic capillary leak syndrome)

Abstract: The systemic capillary leak syndrome (SCLS) is a rare disorder characterized by transient episodes of hypotensive shock and anasarca thought to arise from reversible microvascular barrier dysfunction. Although the high prevalence of a monoclonal gammopathy of unknown significance in SCLS suggests a pathogenic contribution of endogenous immunoglobulins, the mechanisms of vascular hyperpermeability remain obscure. Herein, we report clinical and molecular findings on 23 patients, the largest SCLS case series to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
209
3
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(233 citation statements)
references
References 59 publications
8
209
3
13
Order By: Relevance
“…A previous report 8 and our recent study 17 but not control sera, induced endothelial barrier dysfunction in vitro. 14,15 In contrast, we found elevated levels of IL-8, TNF-a, and CCL2 in pediatric SCLS sera compared with sera from healthy control children, whereas concentrations of VEGF, Ang2, or CXCL10 were not different from controls (Fig 2). However, the absolute levels of all cytokines were much lower in the Sion-Sarid et al 2010 9 Gousseff et al 2011 3 Piastra et al 2012 10 Perme et al 2013 11 Iwasa et al 2014 12 children tested than those seen in adults.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…A previous report 8 and our recent study 17 but not control sera, induced endothelial barrier dysfunction in vitro. 14,15 In contrast, we found elevated levels of IL-8, TNF-a, and CCL2 in pediatric SCLS sera compared with sera from healthy control children, whereas concentrations of VEGF, Ang2, or CXCL10 were not different from controls (Fig 2). However, the absolute levels of all cytokines were much lower in the Sion-Sarid et al 2010 9 Gousseff et al 2011 3 Piastra et al 2012 10 Perme et al 2013 11 Iwasa et al 2014 12 children tested than those seen in adults.…”
Section: Discussioncontrasting
confidence: 42%
“…2,3 Our current and limited understanding of SCLS pathogenesis is that endothelial contraction and adhesive junction remodelling lead to capillary hyperpermeability and subsequent plasma extravasation. 14,15 Although the high prevalence of monoclonal gammopathy of undetermined significance in adult cases raises the possibility of a paraprotein/autoantibody-mediated mechanism, we and others [14][15][16] have been unable to demonstrate a direct pathogenic function of the monoclonal IgG in SCLS. Other soluble factors such as cytokines could also have a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teofyllin og terbutalin fremmer endotelbarrierefunksjon gjennom å stabilisere VE-cadherinmediert adhesjonsjunksjon (adhesive junctions), og de antas også å øke innhold av intracellulaer syklisk adenosinmonofosfat (cAMP) som motvirker kapillaer lekkasje. Tidligere har man ment at bruken av beta-2-agonister fører til reduksjon av kapillaerpermeabilitet indusert ved histamin og bradykinin, men disse inflammasjonsmediatorene har muligens mindre betydning ved idiopatisk systemisk kapillaerlekkasjesyndrom (5).…”
Section: Diskusjonunclassified
“…While Ueda N et al indicated that high level of angiopoietin-2 (Ang2) can be a good indicator of posttransplant endothelial injury; Xie Z et al reported that vascular endothelial growth factor (VEGF) and Ang2 levels were quite high during the attack periods of systemic capillary leak syndrome compared to remission period. 56,57 Capillary leak syndrome generally emerges within the first 15 days of post allo-HSCT, it can also be detected in late periods: it is especially characterized with rapid weight gain (>%3 within 24 hours), ascites non responsive to diuretic treatment and pleural or pericardial effusion that might be a prodrome of common edema development. 33 Renal failure caused by hypoalbuminemia or pre-renal azotemia, hypotension and tachycardia can also accompany to clinic.…”
Section: Capillary Leak Syndromementioning
confidence: 99%